2013
DOI: 10.1186/1752-1947-7-140
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of spontaneous axillary artery aneurysm: a case report and review of the literature

Abstract: IntroductionSpontaneous atraumatic true axillary artery aneurysm is a relatively unusual disorder. Although most cases are asymptomatic, complications of axillary artery aneurysms may result in acute vascular insufficiency and neurological deficits. Prompt treatment, therefore, should be employed in the management of this condition. To date, the standard treatment for peripheral aneurysms is still surgical resection with end-to-end anastomosis. However, aneurysmectomy and interposition grafting with autologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…1 The main causes are arteriosclerosis, thoracic outlet syndrome, infection, blunt trauma, and connective tissue disorders such as Marfan syndrome. 4,7 -10,12 -14,16 However, our patient had none of these. In patients undergoing hemodialysis, arterial aneurysms proximal to AVF are unusual.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…1 The main causes are arteriosclerosis, thoracic outlet syndrome, infection, blunt trauma, and connective tissue disorders such as Marfan syndrome. 4,7 -10,12 -14,16 However, our patient had none of these. In patients undergoing hemodialysis, arterial aneurysms proximal to AVF are unusual.…”
Section: Discussioncontrasting
confidence: 52%
“…These aneurysms are fundamentally treated by a surgical approach, 1,2 -4,7 -10 but endovascular interventions are also currently performed 11 -14 and are associated with less severe complications. 15 Indeed, surgical procedures may result in complications such as organ injury because of the axillary anatomical complexity around aneurysms, including the axillary artery, vein, brachial plexus, internal jugular vein, and major and minor pectoral muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the effectiveness of endovascular repair by a covered-stent or stent-graft for the axillary arterial aneurysm. 8 , 9 ) Reportedly, endovascular treatment is less invasive compared to open surgery and has a low risk of complications caused by a surgical procedure. Hence, this therapy could be considered for patients with anatomical suitability for endovascular device approach and deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the standard treatment for axillary artery aneurysms; however, endovascular methods have become more commonly used in recent years due to emerging techniques and equipment [ 2 10 11 ]. Graft stents have become the procedure of choice for the endovascular treatment of peripheral aneurysms [ 9 ]. However, stent placement near a mobile joint carries the risk of stent deformation or breaking.…”
Section: Discussionmentioning
confidence: 99%